Endometriosis-associated primary clear cell adenocarcinoma of the urinary bladder: A case report and literature review - Meghana Singh; Michael Raver; Bianca DeAgresta; Alexandra Della Pia; Sonam Saxena; Merieme Klobocista; Nitin Yerram (Urology Case Reports)
Primary clear cell adenocarcinoma (CCA) of the urinary bladder is a rare and aggressive malignancy. Few reports in the literature describe this presentation, as associated with malignant transformation of endometriosis. This case highlights the complex etiology of this variant of CCA, initially diagnosed using comprehensive imaging and genetic analysis, and subsequently confirmed through extensive surgical intervention and chemotherapy.